ATTITUDES OF YOUNG PEOPLE ON THE QUALITY OF LIFE IN RURAL ENVIRONMENTS OF THE REPUBLIC OF SERBIA - "NORTH-SOUTH" COMPARISON - Milenković, Milica; Marčetić, Anđela; Jovanović, Tatjana (ACADEMIC REVIEW, 2022)
Observing the life of the population in a specific area, it is impossible to analyze phenomena of any kind, without paying attention to the quality of life, in a direct or indirect sense. Life consists of the entire everyday life with its factors, and the quality of life affects the opportunities offered to the population, and vice versa. In order to examine the quality of life and make, both the initial picture of the apartment, as well as the further examination, it is necessary to examine the relevant indicators, and to logically interpret their values, include them and draw conclusions. The phenomenon of uneven distribution of profits, opportunities for the population and the overall level of economic and economic development, i.e., differences in the "rich north" and the "poor south", can represent a good starting point for further investigations of this kind.